2016
DOI: 10.1007/978-981-10-1503-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Biobanks and Their Clinical Application and Informatics Challenges

Abstract: Biobanks are one of the most important biomedical research resources and contribute to the development of biomarker detection, molecular diagnosis, translational medicine, and multidisciplinary disease research, as well as studies of interactions between genetic and environmental or lifestyle factors. Aiming for the wide clinical application of biobanks, biobanking efforts have recently switched from a focus on accumulating samples to both formalizing and sustaining collections in light of the rapid progress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…They have shown that storage temperature affected metabolite concentrations only little, while the number of temperature change cycles has a strong effect on metabolites stability [110]. Biobanking is considered as a critical component of precision medicine workflow and is being incorporated into several PMIs [112][113][114]. For example, MOBIT project adopted the oncology biobanking procedures developed by a commercial biotech company Indivumed GmbH (Hamburg, Germany) [22].…”
Section: Biobankingmentioning
confidence: 99%
“…They have shown that storage temperature affected metabolite concentrations only little, while the number of temperature change cycles has a strong effect on metabolites stability [110]. Biobanking is considered as a critical component of precision medicine workflow and is being incorporated into several PMIs [112][113][114]. For example, MOBIT project adopted the oncology biobanking procedures developed by a commercial biotech company Indivumed GmbH (Hamburg, Germany) [22].…”
Section: Biobankingmentioning
confidence: 99%
“…This typically includes pathological data collected and reported according to published national guidelines, treatment type (eg, hormone, chemotherapy, radiotherapy or biological therapy), duration of and response to therapy, dates of local, regional and distant recurrence, as well as the date and cause of death plus other comorbidities. However, the challenges surrounding data linkage from electronic health records and informatics for biobanks are well recognised, 43,44 particularly as academic institutes, healthcare systems and biobank networks are frequently separate entities, which may use different informatics platforms which cannot be linked easily. While steps are now being taken by various biobanks to make this process more streamlined, [45][46][47] manual intervention is often still required making this an inefficient and time consuming process.…”
Section: Linking Clinical Data To Biological Samplesmentioning
confidence: 99%
“…Longitudinal prospective cohort studies are conceptually suitable for the discovery of novel biomarkers through collec-tion of adequate data and biological samples before (preclinical), during (clinical), and after disease development. 2,3 The identification of novel biomarkers that can predict treatment response at the patient individual level requires the standardized collection, processing, and storage of biological samples. Biobanking and the new field of biospecimen science have significantly contributed to generating reproducible results in biomedical research.…”
Section: Introductionmentioning
confidence: 99%